The characteristics and mechanisms of carbon finance development on green economic efficiency: an empirical analysis based on endogenous economic growth model - Chen, Yiru; Ma, Guangcheng (Frontiers in Environmental Science, 2024)
The purpose of this paper is to examine whether the development of carbon finance can promote sustainable economic growth in China through spatial spillover effects. On the basis of a theoretical analysis of this mechanism, this paper takes 30 provincial-level administrative regions in China as the research object and uses a variety of spatial econometric analysis techniques to empirically test them. It assesses sustainable economic development measured by green total factor productivity (GTFP). This study documents a significant and positive impact of province-level carbon finance improvement on sustainable economic growth through improving technological progress and increasing technological market turnover. The economic influence of carbon finance on sustainable economic growth is still positive after considering possible endogeneity concerns. Results reveal heterogeneity and spatial spillover effects of carbon finance on GTFP, notably stronger in eastern regions compared to central and western ones. We find that the technological progress and technological market turnover have significant and positive promotional effects on GTFP with increasing levels of carbon finance. This paper provides policy implications for improving sustainable economic development.